Diskursus Pembagian Warisan Bagi Wanita: Kritik Terhadap Tafsir Sosial Al-Qâsimî dalam Mahâsin Al-Ta'wîl - Fatihunnada, Fatihunnada (Universitas Islam Negeri Raden Intan Lampung, 2017)
Discourse of Women Inheritance: A Criticism to al-Qâsimi’s Social Exegesis in Mahâsin al-Ta’wil. This article examines the work of the 19th-century Damascus interpreter, al-Qasimi, in his book entitled Mahâsin al-Ta’wîl. The goal is to see whether there is a link between interpretation patterns of the figure with factors existing in his surrounding environment.. The focus of the study is emphasized on how al-Qasimi interprets verses dealing with certain social issues, especially with the differences in inheritance between men and women. This study concludes that the social condition factors significantly contributes to the formation of his interpretation.